Outreach and screening following the 2005 London bombings: usage and outcomes. - Brewin, C; Fuchkan, N; Huntley, Z; Robertson, M; Thompson, M; Scragg, P; d'Ardenne, P; Ehlers, A (2010)
BACKGROUND: Little is known about how to remedy the unmet mental health needs associated with major terrorist attacks, or what outcomes are achievable with evidence-based treatment. This article reports the usage, diagnoses and outcomes associated with the 2-year Trauma Response Programme (TRP) for those affected by the 2005 London bombings.MethodFollowing a systematic and coordinated programme of outreach, the contact details of 910 people were obtained by the TRP. Of these, 596 completed a screening instrument that included the Trauma Screening Questionnaire (TSQ) and items assessing other negative responses. Those scoring ≥6 on the TSQ, or endorsing other negative responses, received a detailed clinical assessment. Individuals judged to need treatment (n=217) received trauma-focused cognitive-behaviour therapy (TF-CBT) or eye movement desensitization and reprocessing (EMDR). Symptom levels were assessed pre- and post-treatment with validated self-report measures of post-traumatic stress disorder (PTSD) and depression, and 66 were followed up at 1 year. RESULTS: Case finding relied primarily on outreach rather than standard referral pathways such as primary care. The effect sizes achieved for treatment of DSM-IV PTSD exceeded those usually found in randomized controlled trials (RCTs) and gains were well maintained an average of 1 year later. CONCLUSIONS: Outreach with screening, linked to the provision of evidence-based treatment, seems to be a viable method of identifying and meeting mental health needs following a terrorist attack. Given the failure of normal care pathways, it is a potentially important approach that merits further evaluation.